The social media political participation model: A goal systems theory perspective. (February 2020) - Knoll, Johannes; Matthes, Jörg; Heiss, Raffael
Although studies suggest that the use of social media can promote political participation (PP), there is a lack of theorizing about the psychological processes underlying this relationship. This article attempts to fill this gap by suggesting a social media political participation model. Taking a goal systemic perspective, the model specifies a set of interrelated processes that need to be realized so that social media use affects PP. Furthermore, key contingent conditions are outlined and insights into fostering PP are offered. The article explains ways of testing the model with surveys and experiments. Implications for future research are discussed.